Potential applications of nanotechnology for the diagnosis and treatment of pancreatic cancer - McCarroll, Joshua; Teo, Joann; Boyer, Cyrille; Goldstein, David; Kavallaris, Maria; Phillips, Phoebe (Frontiers in Physiology, 2014)
Despite improvements in our understanding of pancreatic cancer and the emerging concept of personalized medicine for the treatment of this disease, it is still the fourth most common cause of cancer death in the western world. It is established that pancreatic cancer is a highly heterogeneous disease with a complex tumor microenvironment. Indeed the extensive stroma surrounding the cancer cells has been shown to be important in promoting tumor growth and metastases, as well as sequestering chemotherapeutic agents consequently decreasing delivery to the tumor cells. Nanotechnology has come to the forefront in the areas of medical diagnostics, imaging, and therapeutic drug delivery. This review will focus on the potential applications of nanotechnology for diagnosis, imaging, and delivery of therapeutic agents for the treatment of pancreatic cancer.